Tagar 2019 Ganti Presiden Dalam Persepsi Netizen - Resita Shabrina; Achmad Herman (Universitas Muhammadiyah Sidoarjo, 2019)
The purpose of this study was to determine the perceptions of netizens towards hashtag 2019GantiPresiden on the Twitter. This type of research is descriptive quantitative approach, with survey methods. The variable studied is a single variable. The respondens in this study were all Following Twitter accounts @resitashabrina which were actively participated by 54 people who used the #2019GantiPresiden. The data analysis technique used in this study uses descriptive analysis through a quantitative approach using frequency distribution assistance to determine the results of the study. Based on the results of research conducted on 54 respondents, namely netizens from all @resitashabrina following accounts about netizens 'perceptions on the Twitter page it can be concluded that netizens' perceptions are seen from stimuli (messages, hashtag knowledge), organisms (understanding, attention, acceptance of Tagar) and response (hashtag effect) on the Twitter page is still quite doubtful, in this case it is said to have not been effective among netizens, especially the following account @resitashabrina as a microblog media with the distribution of scores from each indicator namely the First Stimulus indicator with an overall score of 80.6, Second Organism with an overall score of 68.41 and Third Response with an overall score of 58.3. Other than doubtful assessment is still a large score considering that some answers were written by some respondents with a score distribution of 30.9. So that the netizens' perception of #2019GantiPresiden is still known and conveyed, and still gets the attention of netizens.